Philosophical and epistemological foundations of a post-structural writing lesson - Meisels, Marlene V (Princípios: Revista de Filosofia (UFRN), 2019)
In the world of research or instruction, operating from different philosophical and epistemological traditions results in very different kinds of classrooms. I use a post-structural perspective to show how a teacher could conduct a college developmental writing lesson. Included is an overview of post-structural theory. I suggest one way to accommodate diversity in the classroom is by building both teachers’ and students’ awareness of epistemological positions, because some positions empower students more than others. Another reason for examining epistemologies is to cultivate awareness of the social, religious, political, and other assumptions or agendas with which we enter the classroom.